Innovative aspects of formation of sustainable development and social safety in the socio-cultural context - Garashchuk, Olena; Kutsenko, Vira (Herald of Economics, 2022)
Introduction. The development of modern society is now affected by negative phenomena of natural and social nature, which makes it very important issues of social safety. The best way to achieve it is to implement the principles of sustainable development, which involves a harmonious combination of social, economic and environmental components.The purpose of the study. The purpose of the research presented in this article is to find scientifically sound ways to form social safety and achieve sustainable development in the country.Research methods. To achieve the goal of the study used a set of general scientific methods of cognition, namely: a systematic approach to the study of innovative aspects of sustainable development and social safety; classification and grouping – to analyze the factors contributing to the main goals of sustainable development; tabular – to highlight the components of the socio-economic environment that reflect indicators of social safety; statistical comparison – to assess living standards and in particular the level of food consumption; logical generalization – to substantiate the recommendations and formulate conclusions.The results of the study. As practice has shown, positive changes on the basis of sustainable development are achieved when their main drivers are science and socio- cultural sphere. At the same time, it is important to ensure social safety. Accordingly, the indicators that characterize the socio-economic situation in Ukraine and are indicators of the state of social safety are analyzed. Groups of factors are identified – economic, political, environmental and demographic, taking into account which will enable the successful implementation of the main goals of sustainable development. The necessity of priority development of the sphere of social and cultural services, which should contribute to guaranteeing social safety, is substantiated. The need to implement innovative activities in this direction is emphasized.Conclusions. Today, the innovation aspect must be crucial for sustainable development and social safety based on the development of science, which necessitates the training of professionals working at the level of world standards.Prospects for future research. Further research should be aimed at actively identifying and implementing factors contributing to the strengthening of the socio-cultural sphere in the direction of achieving social safety in Ukraine.